2016
DOI: 10.21833/ijaas.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Blended learning: pedagogy, learning styles, and assessment activities in the classroom

Abstract: A change on the education system is essential in order to produce positive impacts to the success of students; hence, preparing them for the 21st century globalization challenges. The advanced technology nowadays which is both dynamic and futuristic ought to catalyses innovation within the education system of Malaysia. As such, the Ministry of Education (MOE) of Malaysia has taken proactive steps and innovate the education system in line with the current technology. Smart school is one of the results of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
0
8
0
2
Order By: Relevance
“…. Indeks goodness-of-fit is generally used to identify measurement models and structural fit models (Yeop et al, 2016). Based on Hair et al (2017), if the CFI and GFI values are lower than 0.95, the RMSEA value must be <0.05.…”
Section: Research Resultsmentioning
confidence: 99%
“…. Indeks goodness-of-fit is generally used to identify measurement models and structural fit models (Yeop et al, 2016). Based on Hair et al (2017), if the CFI and GFI values are lower than 0.95, the RMSEA value must be <0.05.…”
Section: Research Resultsmentioning
confidence: 99%
“…The unhelpful curriculum, pedagogy, and context end up fostering learner resistance (Huang, 2018). This experience draws a sharp contrast from what was observed that teachers need to understand the nursing students to facilitate teaching (Yeop et al, 2016).…”
Section: Theme 2: Communicative Struggle Within the Divergence Of Reamentioning
confidence: 96%
“…Object-Oriented Dynamic Learning Environment (MOODLE)" [28]. As a reminder, the concept of VS that integrates 'face-to-face' and virtual teaching is called 'blended learning' [29]. Courses are synchronized, providing participants interaction medium in real-time.…”
Section: Conceptual Framework On Virtual Space In Covid-19 Pandemic Dispensationmentioning
confidence: 99%